Memoirs of Louis XIV and His Court and of the Regency $1 (BVolume 03s - Saint-Simon, Louis de Rouvroy, duc de, 1675-1755 (Salt Lake City, UT : Project Gutenberg, 2004)
"Memoirs of Louis XIV and His Court and of the Regency $1 (BVolume 03" by Saint-Simon is a historical account written in the early 18th century, providing an intricate look into the affairs and intrigues surrounding the French court. This volume details significant political maneuvers, including the succession of the Spanish throne and the tumultuous relationships among European monarchies during the reign of Louis XIV. Prominently featured are the Spanish King, his court, and the alliances and conflicts arising from the heir's uncertain future. The opening of this volume delves into the precarious state of the Spanish monarchy as the aging King faces declining health with no heir, stirring fears of power struggles across Europe. William III of England proposes a distribution of territories to avert conflict, igniting fierce political debates and an intricate web of intrigue at the Spanish court. Within this turbulent backdrop, factions emerge, vying for control over the succession, while the influence of the Austrian family looms large, complicating the dynamics amongst the court's elite. The narrative sets the stage for intense conflicts, power plays, and strategic alliances that characterize this critical period of European history, highlighting the intricate relationships and political agendas at play. (This is an automatically generated summary.)s
Release date is 2004-12-03
Produced by David Widger
Keywords: France -- Court and courtiers; France -- History -- Louis XIV, 1643-1715; France -- History -- Regency, 1715-1723